MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH SOAL CERITA MATEMATIKA MELALUI MODEL THINK PAIR SHARE BERBANTUAN CROSSMATH GAME DI KELAS IV SDN RAWAMANGUN 09 - Gardina Syahda Agtyasha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The problem-solving ability of fourth-grade students in solving mathematical word problems is still relatively low, as indicated by students’ difficulties in understanding the problems, determining solution strategies, and drawing conclusions from the given problems. This classroom action research aimed to improve students’ mathematical word problem-solving ability through the implementation of the Think Pair Share (TPS) model assisted by the Crossmath Game. The research was conducted at SDN Rawamangun 09, involving 24 students of class IVB as the research subjects. The classroom action research employed the Kemmis and McTaggart model, which was carried out in two cycles. Data on students’ mathematical word problem-solving ability were obtained through a mathematical problem-solving ability test based on Polya’s indicators, namely understanding the problem, planning the solution, carrying out the plan, and reviewing the solution. The results showed that in Cycle I, the indicator achievement reached 41.66% and increased to 87.50% in Cycle II, exceeding the predetermined achievement criterion of 75%. Based on these findings, it can be concluded that the implementation of the Think Pair Share (TPS) model assisted by the Crossmath Game can improve the mathematical word problem-solving ability of fourth-grade students at SDN Rawamangun 09. The results of this study are expected to serve as an alternative instructional approach for teachers in implementing the Think Pair Share (TPS) model assisted by the Crossmath Game in elementary school mathematics learning.